The effects of fatigue during the take-off phase of basketball lay-up - Chang, J.; Cesario-Ketchum, P.; Hsieh, C. -H. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of the current study was to investigate the effects of fatigue during the takeoff phase of a basketball lay-up. Seven recreational male athletes performed five successful lay-ups during normal and fatigued state. Fatigue was induced by repetitive maximum vertical jumps until subjects failed to reach 80% of maximum vertical jump height. Three-dimensional motion analysis was used to obtain kinematic changes during the take-off phase. Results indicated a significant difference in the knee flexion angle at the instant of contact. Fatigue had no statistical significant effect to the range of motion of knee abduction, hip flexion, ankle flexion angle, and take-off velocity. Additional external factors that affect knee kinematics during a regular basketball lay-up needs to be included as male athletes may counter the effects of fatigue during experimental control.